Education based on Sustainable Development in Islamic Boarding Schools to Address Climate Change - Azka, Moh Shadam Taqiyyuddin; Kubro, Khodijatul; Naimah, Chayul (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to explore the role of sustainable development-based education in Islamic boarding schools in addressing the challenges of climate change. Islamic boarding schools, as influential Islamic educational institutions, have the potential to shape students’ behavior and awareness of the environment. This research focuses on how education in pesantren can be integrated with sustainable development principles to promote environmentally friendly attitudes and actions. The method used in this study is a mixed method that combines qualitative and quantitative approaches. Qualitatively, data were obtained through in-depth interviews with pesantren caregivers, ustadz, and santri, and non-participatory observation of sustainable practices in pesantren, such as waste management and greening programs. Quantitatively, a survey was conducted on a number of santri to measure their level of understanding and participation in environment-related activities. Data from these two methods were analyzed in triangulation to gain a holistic understanding of the implementation of sustainable development-based education in pesantren. The originality of this research lies in its rarely discussed focus, namely the integration of sustainable development education in Islamic boarding schools to address climate change issues. As a traditional educational institution, pesantren are often considered separate from global efforts related to sustainability. This research shows that pesantren can be effective agents of change in raising environmental awareness and facing the challenges of climate change through education based on Islamic values and sustainability principles.